PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERBANKAN YANG TERCATAT DALAM BURSA EFEK INDONESIA - Oktafalia Marisa; Janny Rowena (STIE Wiyatamandala, 2018)
Banking sector has very important role in International Trade and National Development. In Banking sector, this business also generate and reported financial report as the tool to evaluate and control the the fund that they received and they distributed. This financial report also must submitted on time and inform all relevant information regarding the entire business activity base on IASB framework. This punctuality also contributes to the accuracy and efficiency of stock market performance. This research purpose is to examine the effect of profitability, liquidity, capital structure and size of the firm to punctuality of financial report submission on banking sector in Indonesia Stock Exchange. There are 5 independent variables that proxy the financial aspect such as profitability, liquidity, capital structure and size of the firm. This research applied multiple linear regressions and tests the effect of these 5 variables on punctuality of financial report submission. We applied F test, t test and examine R2 value to the model. Finding of this research is only profitability has the effect on punctuality of the financial report submission. While the other variables cannot be concluded has the effect as the p value of variable showed > 0.05. Base on F test, this research also concludes there is simultaneous effect of these 5 variables on punctuality of financial report submission. Keyword : Financial Report Submission; Profitability; Liquidity; Capital Structure; Size of the Firm; Multiple Linear Regression; Banking Services.